Fe Doped Magnetic Nanodiamonds Made by Ion Implantation as Contrast Agent for MRI - Bo-Rong Lin (Nature Portfolio, 2018)
Abstract We report in this paper a new MRI contrast agent based on magnetic nanodiamonds fabricated by Fe ion implantation. The Fe atoms that are implanted into the nanodiamonds are not in direct contact with the outside world, enabling this new contrast agent to be free from cell toxicity. The image enhancement was shown clearly through T2 weighted images. The concentration dependence of the T2 relaxation time gives a relaxivity value that is about seven times that of the regular non-magnetic nanodiamonds. Cell viability study has also been performed. It was shown that they were nearly free from cytotoxicity independent of the particle concentration used. The imaging capability demonstrated here adds a new dimension to the medical application of nanodiamonds. In the future one will be able to combine this capability of magnetic nanodiamonds with other functions through surface modifications to perform drug delivery, targeted therapy, localized thermal treatment and diagnostic imaging at the same time.